STUDENTS' STRATEGIES IN OVERCOMING THE DIFFICULTIES ENCOUNTERED IN SPEAKING: A Descriptive Qualitative Research at MTsS Safinatussalamah - Samhudi Samhudi (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
This research was concerned to find out strategies were used by the eighth grade students of MTsS Safinatussalamah Lhokseumawe to overcome the difficulties in English speaking, and to know the reason they chose those strategies. The design applied in this research was descriptive qualitative research. Meanwhile, the techniques of data collection were observation, field note, and interview. The researcher analyzed the data by Miles and Huberman model, namely data reduction, data display, and conclusion. The result of the research showed that there were various learning strategies used by the students. There were meta-cognitive strategies, cognitive strategies, and social-affective strategies. They chose those strategies based on some reasons, such as because they wanted to check their language to be a good language in speaking, they felt easier to get the ideas in speaking, and they knew their ability in speaking. So, the strategies were very important to help students in learning process especially in learning English speaking. A good strategy also helped the students to learn fun and creative, so that the students would feel interested in learning and they could practice their speaking.